Inhibition of miR-182-5p Targets FGF9 to Alleviate Osteoarthritis. (29th March 2023) - Sun, Yang; Su, Sanmao; Li, Mengjun; Deng, Ang
Abstract : Background . The pathogenesis of osteoarthritis (OA) is complex and there is no specific drug for treatment. The aim of this study was to identify the molecular targets of OA therapy, focusing on the expression and biological functions of miR-182-5p and its target genes in OA. Methods . miR-182-5p and fibroblast growth factor 9 (FGF9) were overexpressed or knocked down in IL-1 β -induced chondrocytes. An OA knee model was performed by surgically destroying the medial meniscus. The gene expression of miR-182-5p and FGF9 was calculated. The protein FGF9 was tested by western blotting. Cell counting kit-8 (CCK8), plate cloning assay, and flow cytometry were conducted to evaluate cell proliferation and apoptosis. The expression of inflammatory factors, tumor necrosis factor-alpha (TNF- α ), interleukin (IL)-6, and interleukin (IL)-8, was evaluated using enzyme-linked immunosorbent assay (ELISA). Dual-luciferase reporter assays validated the targeting relationship between miR-182-5p and FGF9. Hematoxylin–eosin (HE) and safranin O-fast Green (S–O) staining were utilized to access cartilage damage. Ki67 expression in cartilage was detected using immunohistochemistry (IHC). TdT-mediated dUTP nick-end labeling (TUNEL) assays were used to calculate the apoptosis rate of cartilage. Results . The expression of miR-182-5p was upregulated, and FGF9 was downregulated in the IL-1 β -induced chondrocytes. OA chondrocytes proliferation ability in the miR-182-5p mimics group was decreased, and the apoptosis rate and inflammatory factor were increased. Transfection with miR-182-5p inhibitor increased the proliferative ability and decreased the apoptosis rate in the IL-1 β -induced chondrocytes. Transfection with miR-182-5p inhibitor reversed IL-1 β -induced inflammatory factor release in chondrocytes. Targeted binding sites existed between miR-182-5p and FGF9. After overexpression of FGF9, the miR-182-5p effect on OA chondrocytes was reversed. The hyaline cartilage thickness and proteoglycan content decreased in OA rats, and this was reversed by miR-182-5p inhibitor treatment. Conclusions . miR-182-5p expression levels were increased in OA chondrocytes and regulated chondrocyte proliferation, apoptosis, and inflammation by targeting FGF9. miR-182-5p is a potential gene for OA treatment.